Self-Care Education on the Pain, Quality of Life, and Consequences of Disease in Patients with Knee Osteoarthritis - Zeinab Jokar PhD; Zahra Hosseinabadi MS; Sanaz Rustaee MS; Mostafa Bijani PhD (SAGE Publishing, 2024)
Introduction Knee osteoarthritis (KOA) is one of the most common and prevalent debilitating chronic diseases across the world with various adverse effects such as pain and movement limitations which impact the health status and quality of life of the patients in the long run. Objectives This study aimed to investigate the effects of self-care education on pain, quality of life, and consequences of disease in patients with KOA in Southern Iran. Methods This is a randomized controlled clinical trial using a pretest-posttest design. Eighty patients with KOA were enrolled in this study and randomly allocated to a control and an intervention group. The data collection instruments included VAS: Visual Analog Scale, the SF-36 quality of life scale, and the Knee Injury and Osteoarthritis Outcome Score. The collected data were analyzed through SPSS v. 22, using descriptive tests, paired t -tests, independent t -tests, Chi-square, and ANOVA. A P level of <.05 was considered as the significant level. Results Before the self-care educational intervention, no statistically significant difference was found between the control and intervention groups in pain intensity, quality of life, and consequences of osteoarthritis. After the self-care educational intervention, the findings revealed a significant difference between the intervention group's mean ± standard deviation for pain intensity (41.25 ± 21.74), quality of life (49.87 ± 14.74), and consequences of KOA (39.06 ± 12.15), respectively ( P  < .05). However, in the control group, there was no significant difference. Conclusion Based on the results of this study, the positive effect of self-care education on patients with osteoarthritis was shown as to their pain intensity, quality of their lives, and reduction of the disease consequences. Thus, healthcare managers are recommended to apply this type of intervention for patients with osteoarthritis.